Temperature effect on polymerization kinetics of polystyrene - Siti At Thahirah, Hasanul Ridza (2013)
This research is to study temperature effect on polymerization kinetic of polystyrene. The purposes of this research are to study temperature effect on polymerization kinetics of polystyrene. The experiments for this research were conducted in bulk polymerization of styrene. In this experiment, the temperature will be changing and the value of initiator is constant. Firstly, 3mg of styrene and 2mg of azobisisobutyronitrile solution (in toluene) are placed into the pan. Then, the pan is put into the Differential Scanning Calorimetry at the required temperature. The graph for heat flow versus time is recorded by Differential Scanning Calorimetry software until the reaction is complete. By referring to the graph it can be seen that the reaction rate of polymerization increase with the increase of temperature. As a conclusion, from this research, it can be seen that changing the temperature can affect polymerization kinetic of styrene.